Acaricidal activity of five essential oils against Rhipicephalus annulatus ticks and their GC-MS analyses - Abeer Moawad, Elham Amin, Waleed Arafa, Khaled Hussein, Khaled Hassan, Asmaa Owis, Hayam Ahmed (Journal of Applied Pharmaceutical Science, 2024)
Rhipicephalus annulatus is regarded as the most common tick in transmitting cattle disease. Chemical acaricides resistance and toxicity have directed research on the use of essential plant oils which have great potential for pest management for safe food production. Therefore, the current study was designed to test the larvicidal activity of essential oils (EOs) of five medicinal plants; cilantro leaves, orange leaves, Tagetes flower, geranium herb, and sweet basil herb against R. annulatus larvae using the larval packet test. Analysis of EO chemical composition using gas chromatography-mass spectrometry (GC-MS) was also carried out to justify the assigned activities. Cilantro, orange, and Tagetes EOs showed 100.0% larval mortality with lethal concerntrations that kills 50% (LC50) of 1.46%, 0.88%, and 2.94%, respectively. Geranium and sweet basil herbs EOs showed 96.33% ± 3.18% and 92.33% ± 1.45% larval mortality with LC50 of 5.28% and 7.20%, respectively. Major compounds were identified by GC-MS as follows, [2(E)-decenal (49.72%), decanal (21.47%)] from cilantro EO, [methyl methanthranilate (63.45%), γ-terpinene (18.64%)] from orange EO, [trans-β-ocimene (24.93%) and isoartemisia ketone (8.84%)] in Tagetes EO, [β-citronellol (41.83%), citronellyl formate (10.41%), geraniol (9.47%)] from geranium EO, and [β-Linalool (55.63%), 1,8-cineole (9.66%)] from sweet basil. Our results showed the potential of EOs as eco-friendly and economic acaricides for tick control.
Keywords: Cattle disease, natural acaricides, Rhipicephalus annulatus, LPT, essential oils, GC-MS